Harnessing the Glucosyltransferase Activities of Clostridium difficile for Functional Studies of Toxins A and B - Darkoh, Charles (American Society for Microbiology, 2011)
The incidence of Clostridium difficile infection (CDI) has been increasing within the last decade. Pathogenic strains of C. difficile produce toxin A and/or toxin B, which are important virulence factors in the pathogenesis of this bacterium. Current methods for diagnosing CDI are mostly qualitative tests that detect either the bacterium or the toxins. We have developed an assay (Cdifftox activity assay) to detect C. difficile toxin A and B activities that is quantitative and cost-efficient and utilizes a substrate that is stereochemically similar to the native substrate of the toxins (UDP-glucose). To characterize toxin activity, toxins A and B were purified from culture supernatants by ammonium sulfate precipitation and chromatography through DEAE-Sepharose and gel filtration columns. The activities of the final fractions were quantitated using the Cdifftox activity assay and compared to the results of a toxin A- and B-specific enzyme-linked immunosorbent assay (ELISA). The affinity for the substrate was >4-fold higher for toxin B than for toxin A. Moreover, the rate of cleavage of the substrate was 4.3-fold higher for toxin B than for toxin A. The optimum temperature for both toxins ranged from 35 to 40°C at pH 8. Culture supernatants from clinical isolates obtained from the stools of patients suspected to be suffering from CDI were tested using the Cdifftox activity assay, and the results were compared to those of ELISA and PCR amplification of the toxin genes. Our results demonstrate that this new assay is comparable to the current commercial ELISA for detecting the toxins in the samples tested and has the added advantage of quantitating toxin activity.